Antioxidant Intake and Biomarkers of Asthma in Relation to Smoking Status—A Review - Naser A. Alsharairi (Current Issues in Molecular Biology, 2023)
Asthma is considered a chronic inflammatory disorder associated with airway hyperresponsiveness (AHR). Increased oxidative stress (OS) is a clinical feature of asthma, which promotes the inflammatory responses in bronchial/airway epithelial cells. Smokers and nonsmokers with asthma have been shown to have increases in several OS and inflammatory biomarkers. However, studies suggest significant differences in OS and inflammation biomarkers between smokers and nonsmokers. A few studies suggest associations between antioxidant intake from diet/supplements and asthma in patients with different smoking status. Evidence is lacking on the protective role of antioxidant vitamin and/or mineral consumption against asthma by smoking status with respect to inflammation and OS biomarkers. Therefore, the aim of this review is to highlight current knowledge regarding the relations between antioxidant intake, asthma, and its associated biomarkers, according to smoking status. This paper can be used to guide future research directions towards the health consequences of antioxidant intake in smoking and nonsmoking asthmatics.